Term Limits and Political Dynasties in the Philippines: Unpacking the Links - Mendoza, Ronald U. (Animo Repository, 2020)
This paper reviews the empirical evidence linking political dynasties in the Philippines to the imposition of term limits under the 1987 Constitution. It finds evidence that political clans have found a way around this Constitutional constraint by fielding more family members in power—giving rise to more fat political dynasties. Hence, we carefully argue that the introduction of term limits—combined with the failure to introduce other ancillary reforms (notably an anti-dynasty law)—may have brought about instead some unintended consequences. So, it is not term limits per se that created fat political dynasties. We further argue that it is a non sequitur to argue that dynasties will be curbed by removing term limits. This is particularly true given fat political clans are already prevalent, and removing term limits will secure the political foothold of many already fat political dynasties. To illustrate their expansion, we use network analysis and illustrations of power concentration over time in particular jurisdictions. We conclude that real reforms should be focused not on removing term limits, but on further strengthening those reforms that should have accompanied it, including enhancing competition in the political sphere, such as by supplying alternative leaders, strengthening political parties, and regulating political dynasties.